2020
DOI: 10.1101/2020.03.30.015529
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Induction of hyperandrogenism and insulin resistance differentially modulates ferroptosis in uterine and placental tissues of pregnant rats

Abstract: Ferroptosis, a form of regulated necrotic cell death, plays roles in diverse physiological processes and diseases. Women with polycystic ovary syndrome (PCOS) have hyperandrogenism and insulin resistance (HAIR) and an increased risk of miscarriage and placental dysfunction during pregnancy. However, whether maternal HAIR alters mechanisms leading to ferroptosis in the gravid uterus and placenta remains unknown. Previous studies in rats showed that maternal exposure to 5α-dihydrotestosterone (DHT) and insulin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Moreover, Zhang and colleagues reported that maternal HAIR activates ferroptosis in the placenta and gravid uterus through distinct mechanisms. Also, they showed that other cell death mechanisms may be involved in the coordination or compensation of HAIR-induced ferroptosis in the dysfunctional placenta and gravid uterus [45].…”
Section: Trends Trends In In Endocrinology Endocrinology and Metaboli...mentioning
confidence: 99%
“…Moreover, Zhang and colleagues reported that maternal HAIR activates ferroptosis in the placenta and gravid uterus through distinct mechanisms. Also, they showed that other cell death mechanisms may be involved in the coordination or compensation of HAIR-induced ferroptosis in the dysfunctional placenta and gravid uterus [45].…”
Section: Trends Trends In In Endocrinology Endocrinology and Metaboli...mentioning
confidence: 99%
“…MOTS-c treatment of GDM mice was also associated with re-duced blood glucose levels and reduced offspring mortality compared to GDM controls without administered MOTS-c [43]. It is worth noting that administration of insulin in adult female Sprague-Dawley rats leads to a significant decrease in MOTS-c protein levels in both uterine and placental tissues [44,45]. Moreover, lipid infusion significantly increases plasma MOTS-c in healthy women and patients with polycystic ovary syndrome (PCOS); however, insulin administration suppresses lipid-induced increase of MOTS-c protein levels in plasma [46].…”
Section: Pancreasmentioning
confidence: 84%